Metabolic Bone Disease of Prematurity: Diagnosis and Management - Faienza, Maria Felicia; D'Amato, Elena; Natale, Maria Pia; Grano, Maria; Chiarito, Mariangela; Brunetti, Giacomina; D'Amato, Gabriele (Frontiers in Pediatrics, 2019)
Metabolic Bone Disease (MBD) of prematurity is a multifactorial disorder commonly observed in very low birth weight (VLBW, <1,500 g) newborns, with a greater incidence in those extremely low birth weight (ELBW, <1,000 g). MBD is characterized by biochemical and radiological findings related to bone demineralization. Several antenatal and postnatal risk factors have been associated to MBD of prematurity, although the main pathogenetic mechanism is represented by the reduced placental transfer of calcium and phosphate related to preterm birth. The diagnosis of MBD of prematurity requires the assessment of several biochemical markers, radiological, and ultrasonographic findings. However, the best approach is the prevention of the symptomatic disease, based on the screening of subjects exposed to the risks of developing MBD. Regarding the subjects who need to be screened, there is a substantial agreement on the potential risk factors for MBD. On the contrary, different recommendations exist on the diagnosis, management and treatment of this disorder of bone metabolism. This review was aimed at: (1) identifying the subjects at risk for MBD of prematurity; (2) indicating the biochemical findings to take in consideration for the prevention of MBD of prematurity; (3) suggesting practical recommendations on nutritional intake and supplementation in these subjects. We searched for papers which report the current recommendations for biochemical assessment of MBD of prematurity and for its prevention and treatment. The majority of the authors suggest that MBD of prematurity is a disease which tends to normalize overtime, thus it is not mandatory to mimic the rate of mineral fetal accretion through parenteral or enteral supplementation. The optimization of total parenteral nutrition (TPN) and the early achievement of a full enteral feeding are important goals for the prevention and management of MBD of prematurity.